2013
DOI: 10.5089/9781484389041.001
|View full text |Cite
|
Sign up to set email alerts
|

Capital Flows are Fickle: Anytime, Anywhere

Abstract: Has the unprecedented financial globalization of recent years changed the behavior of capital flows across countries? Using a newly constructed database of gross and net capital flows since 1980 for a sample of nearly 150 countries, this paper finds that private capital flows are typically volatile for all countries, advanced or emerging, across all points in time. This holds true across most types of flows, including bank, portfolio debt, and equity flows. Advanced economies enjoy a greater substitutability b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
4
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 13 publications
1
105
4
11
Order By: Relevance
“…Furthermore, net capital flows to and from Switzerland exhibit significantly higher volatility since the global financial crisis, suggesting a decoupling of capital inflows and outflows. This finding contrasts with the long-run trends presented in previous literature, such as BRONER et al (2013) and BLUEDORN et al (2013). As BRONER et al (2013) show, capital inflows to and capital outflows from advanced economies have historically been positively correlated, resulting in small and stable net flows because of their opposing effects.…”
Section: Introductioncontrasting
confidence: 96%
“…Furthermore, net capital flows to and from Switzerland exhibit significantly higher volatility since the global financial crisis, suggesting a decoupling of capital inflows and outflows. This finding contrasts with the long-run trends presented in previous literature, such as BRONER et al (2013) and BLUEDORN et al (2013). As BRONER et al (2013) show, capital inflows to and capital outflows from advanced economies have historically been positively correlated, resulting in small and stable net flows because of their opposing effects.…”
Section: Introductioncontrasting
confidence: 96%
“…The existing empirical literature seems to suggest that flows should indeed weaken as the Fed raises policy rates. Many studies have found that U.S. interest rates are a key driver of capital flows to EMs (e.g., Fernandez-Arias 1996; Taylor and Sarno 1997;Baek 2006;De Vita and Kyaw 2008;Bluedorn et al 2013). The common interpretation of the existing empirical findings is that low U.S. interest rates tend to "push" capital to EMs, while higher interest rates reduce those flows.…”
Section: Introductionmentioning
confidence: 74%
“…Baek (2006) argues that while low returns on "riskless" U.S. Treasury securities boost portfolio investment in emerging markets, low returns on riskier global equity markets have the opposite impact. Bluedorn et al (2013) find that both non-resident capital inflows to emerging markets and resident capital outflows increase when interest rates in advanced economies are low.…”
Section: Literature Overviewmentioning
confidence: 96%
“…Forbes and Warnock (2012) distinguish between surges, stops and retrenchment as different episodes of capital flows since 1980. When focusing on the underlying effects, our quarterly panel VAR approach differs from previous studies which often rely on annual data and focus on correlation rather than causality (Bluedorn et al, 2013) or restrict the analysis on panel regressions neglecting lagged interdependencies between the cross-section units (Blanchard et al, 2015b). A consequent causality analysis of capital flow impacts on GDP which also addresses international spillovers in a fully endogenous and time-varying framework still presents a gap in the literature.…”
Section: Capital Flows and Previous Literaturementioning
confidence: 83%
“…Finally, a somehow surprising result is that the differences between net and gross flows essentially display a similar im-pact. Although gross capital flows tend to be more pro-cyclical and more volatile than net inflows (Bluedorn et al, 2013), the similar impact on GDP suggests that volatility of capital flows does not transmit into significant GDP effects.…”
Section: Time-variation In the Coefficientsmentioning
confidence: 94%